DISKURSUS TENTANG ALLAH MENCIPTA MANUSIA DAN IMPLIKASINYA DALAM HIDUP (ANALISIS FILOSOFIS ATAS KEJ 1:26-27) - Yuliana Jaimut; Agustinus Masterinus Laka Meko (Aggiornamento, 2022)
Philosophy of religions talk about God in a rational level. This does not conflict with the theology or religious faith. In this case the author reverses this, namely approaching the text of faith from a philosophical side. The goal is the same, to find a rational basis for God. The search for God is focused on God as the creator and his relevance to human life. God created man in his image and likeness. Image in Hebrew is called tselem and appearance as demut (Gen 1:26-27). Tselem and demut are studied philosophically by approaching the text as a literary work. The text of Genesis 1:26-27 is then juxtaposed with the teachings of Platonism about the creation of the universe. The meaning found is that image is a natural gift for each person and appearance is a process of becoming image of God. The implication is that everyone is an image of God. As the image of God he deserves respect. Since man is the image of God, every human being also radiates the face of God. To quote St. Augustine that all humans although evil, he is still the image of God. In addition, the concept of God as creator proves that evil and atheism cannot be rationally accepted. Thoughts about God the creator of man contain actual truths and are not obsolete in history. Image and similar is an expression of the deep relationship between humans and God and each other